Combining ability for fruit set in macadamia cultivars - Sacramento, Célio Kersul do; Pereira, Fernando Mendes; Perecin, Dilermano; Sabino, José Carlos (Pesquisa Agropecuaria Brasileira, 1999)
A 5 x 5 diallel experiment was conducted at Experimental Station of Tietê, SP, aiming to evaluate the combining ability amongst macadamia nut trees (Macadamia integrifolia Maiden & Betche) cultivars IAC Campinas A, IAC 2-23 A, IAC 4-12 B, IAC 4-20 e IAC 5-10. The initial fruit set was evaluated 14 days after manual pollination and showed that every cultivar presented self incompatibility. There were significant general and specific combining ability amongst cultivars and reciprocal effects. The cultivar IAC Campinas A reduced the initial fruit set at all crossing in which was used as female progenitor. The best results for initial fruit set were showed by crossings between following cultivars: IAC 4-20 x IAC Campinas A, IAC 4-12 B x IAC 2-23 A, IAC 4-20 x IAC 4-12 B, IAC 5-10 x IAC 2-23 A, IAC 5-10 x IAC 4-20, IAC 4-20 x IAC 2-23 A e IAC 5-10 x IAC 4-12 B.